PROSES PENGELOLAHAN MENINGKATKAN AKTIVITAS HIPOLIPIDEMIK JAMUR TIRAM (PLEUROTUS OSTREATUS) PADA TIKUS (RATTUS NORVEGICUS) SPRGUE-DAWLEY HIPERKOLESTEROL - Eni Harmayani, Deera Army Pramana, Sri Anggrahini dan Sutikarini (Jurnal Teknosains, 2012)
Oyster mushroom is considered to have hypocholesterolemic and hypolipidemic activities. Therefore, it is classifiedas functional food. Prior to serving and consumption, oyster mushroom can be processed in various ways. Thisresearch studied the effect of three kinds of processing commonly used in cooking oyster mushroom; boiling,frying, and roasting. Thirty Sprague-Dawley male rats, 8 weeks old, were acclimated to laboratory condition,and then induced with high lipid diet. The rats were divided into five experiment groups; high-lipid diet (K),high-lipid diet + raw oyster mushroom (M), high-lipid diet + fried oyster mushroom (G), high-lipid diet + roastedoyster mushroom (P), and high-lipid diet + boiled oyster mushroom (R). Blood samples were obtained from orbitalplexus after acclimation, hypercholesterolemic induction, and 21 days of feeding. The blood serum was examinedfor total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-c), dan high-densitylipoprotein cholesterol (HDL-c). The result showed that cooked oyster mushroom had better hypocholesterolemicand hypolipidemic activity than raw oyster mushroom. Among the three, the roasted oyster mushroom reduced thetotal cholesterol the most, while boiled oyster mushroom reduced triglyceride the most.